LITERATURE EXPOSURE IN ENGLISH LANGUAGE TEACHING AND LEARNING - Erly Wahyuni (Soegijapranata Catholic University, 2011)
Teachers often regard literature as inappropriate to the language classroom. Teaching literature in foreign language classroom becomes essential if teachers are concerned with the meaningful foreign language learning activities experienced by the students. It is not sufficient to only emphasize on acquiring mastery of structure andform but also involves acquiring the ability to interpret literary discourse in all its social and cultural contexts. Accordingly, this study focuses on literature exposure in English language teaching and learning. This study which is a descriptive qualitative study was endorsed the data from two sources: namely is the English lecturer and the students of the English Department of UMM The instruments used included interview and questionnaire. The result of the analysis indicates literature exposure has an essential role in English language learning because it is beneficial to the learners' linguistic development, create opportunities for personal expression as well as reinforce students' knowledge of lexical and grammatical structure. Moreover, it becomes important for English teacher to consider cultural contexts into their English language teaching. Students should be given the opportunity in the selection of materials and classroom activities that can expose and enhance students' literary knowledge and understanding.